Dietary oils modify lipid molecules and nutritional value of fillet in Nile tilapia: A deep lipidomics analysis - Liu, Yan; Jiao, Jian-Gang; Gao, Shuang; Ning, Li-Jun; Mchele Limbu, Samwel; Qiao, Fang; Chen, Li-Qiao; Zhang, Mei-Ling; Du, Zhen-Yu (Food chemistry, 2019)
•Dietary oils affect positional distribution of fatty acids in glycerolipids in fish.•Dietary 16:0 and 18:1n-9 are easily utilized for energy supply in Nile tilapia.•Tilapia specifically accumulates high 18:2n-6 and low 18:3n-3 in phospholipids.•Fish oil intake raises deposition of EPA + DHA at sn-1/3 in triglyceride in tilapia.•Nutritional value of fish fillets could be regulated by changing dietary oils. The nutritional value of fish fillet can be largely affected by dietary oils. However, little is known about how dietary oils modify lipid molecules in fish fillets. Through biochemical and lipidomics assays, this study demonstrated the molecular characteristics of fillet lipids in Nile tilapia fed with different oils for six weeks. High 18:2n-6 and low 18:3n-3 deposition in phosphoglycerides resulted high 18:2n-6/18:3n-3 ratio in tilapia. Dietary n-3 VLCUFAs intake increased its deposition at sn-1/3 of triglycerides and at sn-2 of phosphatidylcholines. Irrespective of dietary oil, 16:0 was distributed preferentially at the outer positions of glycerol backbone. High 18:2n-6 accumulated at sn-2 position for fish fed with n-3 PUFA-enriched oils. High 18:3n-3 deposited at sn-1/3 in TG, sn-1 in phosphatidylethanolamines, while at sn-2 in phosphatidylcholines. Together, dietary oils change the composition and positional distribution of fatty acids on the glycerol backbone, and change nutritional value of fish for human health.